KONSTRUKSI DIRI PELAKU BUNUH DIRI YANG GAGAL, DALAM MEMAKNAI KEHIDUPAN DAN KEMATIAN - Syahputra, Muhammad Rizal (Paradigma, 2021)
Suicide is a social phenomenon that to this day is one of the biggest causes of death in all corners of the world. Suicide as a social fact is still a taboo subject to discuss in people’s lives in general. As a sociological phenomenon, suicide has a very close relationship with regulation and social integration, so that suicide cannot be viewed solely as a personal phenomenon. The suicide rate in social life is influenced by these two social facts. Suicide desire is owned by anyone, regardless of class, gender, religion, social class, race, ethnicity, and culture though. The study of suicide in sociology was first introduced by Emile Durkheim in his book entitled "Suicide: A Study of Sociology" published in 1897. In this study I used qualitative research methods, with a theoretical basis from a book written by Emile Durkheim. This study aims to understand the self-construction of the perpetrators of suicide attempts who decide to survive in their meaning of life. I hope that this research will be able to contribute to the development of science, help solve the mystery of the phenomenon of suicide and furthermore can be a solution to prevent suicide tragedies in the future. Keywords: Suicide, self construction, social regulation, social integration.